Navigating socio-ecological and institutional barriers to antiretroviral therapy adherence: qualitative insights among young men and women from Nairobi’s informal settlements - Muhenje, O.; Olungah, C. O.; Omia, D. O.; Ondondo, R. O.; Waswa, P.; Lusambili, A. (Frontiers in Public Health, 2025)
BackgroundThe Human Immunodeficiency Virus (HIV) and acquired immunodeficiency syndrome (AIDS) pandemic remains a major global health issue, with 40.8 million people affected at the end of 2024. In Sub-Saharan Africa, Antiretroviral Therapy (ART) coverage reached 74%, though adherence remained challenging, particularly among youth due to poverty, stigma, and weak health systems.AimThis paper explored socio-ecological and institutional barriers to ART adherence among young men and women aged 18–24 living in Kibra, Nairobi’s largest informal settlement.MethodsThe study utilized phenomenological research design to explore lived experiences within social contexts to uncover hidden structural barriers using qualitative methods. In-depth interviews (n = 25), key informant interviews (n = 10), participant diaries (n = 25), structured clinic and home observations (n = 25), and case narratives (n = 10). Participants were purposively selected. Data were analyzed thematically using deductive and inductive coding in NVIVO 14.Results and discussionBarriers emerged at individual, socioeconomic, and health system levels. These included limited ART knowledge, pill burden, comorbidities, food insecurity, stigma, violence, and negative healthcare provider attitudes. Addressing these requires multi-level interventions that go beyond medical treatment to tackle structural and social determinants of health.